Evidence for the validity of the composite scale of morningness based on students from Germany and Poland: relationship with sleep-wake and social schedules - Randler, Christoph; Jankowski, Konrad S. (Biological rhythm research, 2014)
Morningness-eveningness preference can be measured by questionnaires, such as the Composite Scale of Morningness (CSM). Here, we used data from a retrospective sleep-wake diary including many aspects of social life during the preceding week to establish further convergent quality for the CSM. Participants (N = 570) were students of social science from universities in Warsaw and Heidelberg. Morning-orientated students woke up, got up and went to bed and slept at earlier hours than more evening-orientated students, and experienced less social jetlag. Exceptions were sleep onset latency and sleep duration which seemed unrelated to morningness-eveningness. More morning subjects, as indicated by CSM scores, had earlier first contact with another person, went outdoors earlier and started work earlier. They also had earlier timing of breakfast, lunch and dinner. The correlations between CSM scores and activity indices did not differ between Poland and Germany. The data suggest that morning-orientated students exhibiting greater morningness preference do, indeed, live on an earlier schedule.